Khoáng sản đi kèm trong các kiểu quặng Chì Kẽm và Đồng Miền Bắc Việt Nam - Hòa, Trần Trọng; Anh, Trần Tuấn; Dung, Phạm Thị; Hùng, Trần Quốc; Niên, Bùi Ấn; Hiếu, Trần Văn; Cẩn, Phạm Ngọc (Vietnam Journal of Earth Sciences, 2012)
SUMMARY By-products in lead-zinc and copper ores of Northeast Vietnam By-products in lead-zinc ores are diversify, depending on ore types: Cho Don type - Cd, In, Ag, As, Cu, Sn, Ga ; Cho Dien type - Cd, In, Ag, Cu, Ga ; Lang Hich type - Cd, Ag ; Na Son type : Cd, Ag, Cu, Ga, REE. Detailed mineralogical investigation reveals that by-product elements are mainly associated with inclusions and isomorphous substitution in major ore minerals - galenite and sphalerite, except Cu and As are in distinct minerals. Thus, the extraction of major valued elements (Cd, In, Ag, Sn, and Ga) in lead-zinc ores is strongly relying on leadzinc metallurgic techniques. By-products of the Sin Quyen copper ores consist of : Au, Fe, REE, Ag, Te-Se and Ga. Noteworthy that the extraction of Ag, Te-Se, Ga can be done during the copper metallurgy, whilst REE must be extracted from sifting processes.